O desenho-imagem: entre[linhas]de uma poética - Alcântara, Luciana Azambuja (2010)
The study proposes a work-installation in the context of visual poetry. Combinatorial games images in the digital and analog resources (technological) from drawings of linear features, built by manually modeling wire where the process is effective in passage between the threedimensionality and flatness generating possibilities and creating a new way of seeing the object, now called the design-image. In the process the crossing of the languages of design (and tri-dimensional) and photography were consolidated through digital media. Trajectories woven between the lines of the drawing, the plots, overlays, mixtures, allowed to explore compositional variables in the space of construction, the seizure of the image by digital photography. The plots to infinity, build up false ceilings or limits through the line, tensioning and drawing, each assembly, new lands, fragments of a whole, creative possibilities and repetition. In practice, [between] crosses crosses generate linear mixtures of languages, materials and actions through the images. Among the procedures performed, the study covered the inset, the reasoning and reflection informed decisions in different authors, related to the specific use of the image on the visual and the reproducibility, repetition, time and space, the photograph and the productions that cover the bias of art and technology. The investigation led to the nearest recurring issues and concepts in contemporary art, contributing to the theoretical understanding of concepts and key considerations for research.